IS COVID-19 PANDEMIC A RISK FACTOR FOR MENTAL DISORDERS IN WOMEN DURING PERINATAL PERIOD? - Saiter Luna, Alan; Clara Gomes Braga, Ana; Carvalho Ribeiro, Christiane; Leandro de Oliveira, Edgard; Correa, Humberto; Lino Quintela, Kyze; Geraldo dos Santos Xisto, Lázaro; Lemos Oliveira, Maria Clara; Araújo Fortuna Cáus, Victor (Health and Society, 2021)
COVID-19 pandemic seems to be associated with increased incidence in mental health disorders in pregnant women. Cross-sectional studies identified control measures, social isolation and recurrent fear of COVID-19 infection may rise risk of depression and suicidality in this specific population. Considering the consequences of the pandemic to health systems, such as saturation and the removal of health professionals, it is crucial to discuss and develop new strategies to maintain antenatal and psychiatric follow-ups to help prevent and treat impairments; teleconsultations may be an alternative to keep contact with these patients. Also, in anticipation of COVID-19 fourth wave (which includes increasing psychiatric disorders) it is important to strengthen mental health services to help absorb this demand.